PUBLIC-PRIVATE INVESTMENT SUSTENANCE: TIME SERIES EVIDENCE FROM EDUCATION SECTOR OF PAKISTAN - Khawaja Asif Mehmood; Sonia Shahzadi; Muhammad Zahir Faridi; Muhammad Rizwan Khursheed (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This study relates with the government and private sector partnership in the education sector of Pakistan. For the analyses, the data ranging from 1980 to 2022 is relied upon. For the regression estimation, Autoregressive Distributed Lag (ARDL) approach is used. The explained variable is Government Education Expenditure (GED). The core explanatory variable is Private Education Expenditure (PED). The results show positive relationship between GED and PED. Therefore, as a policy recommendation, the verdict is to strengthen the bonding of public and private partnership especially in the education sector for the better interest of the aspirants of education in Pakistan.